Mechanical Properties of Expansive Soil Stabilized by Sand - Rahayu.J, Tri Kurnia; Herius, Andi; Mulyanda, Dhevi; Anggraini, Nita; Nadiareta, Akifah; ashifah, Anisah Qanitah (Universitas Negeri Padang, 2023)
Expansive clay soils have swelling and shrinkage properties and somehow reduce the mechanical properties required for soils to be used in civil engineering works. One method to improve the soil is by mechanical stabilization, namely mixing expansive clay soil with sand material. The sand material used in this research varied by 7.5%, 15%, and 22.5% of the total dry weight of expansive clay. The results shows that changes in mechanical properties were observed from the compaction test and California Bearing Ratio (CBR) both for soaked or unsoaked test. Based on these variations, in the compaction test, the addition of sand variations increases the maximum dry unit weight value and generally reduces the optimum water content value. The same results were also seen in the soaked and unsoaked CBR tests. In the swelling potential test, the addition of sand material succeeded in reducing the swelling value in expansive clay soils.